Facebook usage habits of diploma students in the classroom: A case study / Norulhuda Tajuddin, Mohamad Ridhuan Mat Dangi and Rahimah Abd Wahab - Tajuddin, Norulhuda; Mat Dangi, Mohamad Ridhuan; Abd Wahab, Rahimah (2013)
Facebook has been widely accepted in recent years as a medium for teaching and learning to replace the traditional classroom approach. There are a few Facebook tools that have been identified by previous researchers that simplify the process of distributing information including tools for the purpose of photos and video sharing, creating groups, creating documents, and so on. The aim of this study is to investigate the Facebook usage habit of45 diploma students in Universiti Teknologi Mara, Pahang who had registered for the MGT 315 Creative and Critical Thinking course as a case study. This study reports on the actual practice of Facebook use in the classroom and attempts to answer the following questions; (1) what are the Facebook usage habit of the students? (2) What are the most preferred Facebook tools used by the students? This study employs descriptive statistical methods such as percentages and mean scores in order to understand the students' habit in using Facebook for academic purposes. The findings of this research explain the Facebook usage habit among the students in the particular course.